Dyslexic Children Have Abnormal Brain Lactate Response to Reading-Related Language Tasks - Richards, Todd L. (AJNR Am J Neuroradiol, 1999)
BACKGROUND AND PURPOSE: Children with dyslexia have difficulty learning to recognize written words owing to subtle deficits in oral language related to processing sounds and accessing words automatically. The purpose of this study was to compare regional changes in brain lactate between dyslexic children and control subjects during oral language activation. METHODS: Brain lactate metabolism was measured during four different cognitive tasks (three language tasks and one nonlanguage task) in six dyslexic boys and in seven control subjects (age- and IQ-matched right-handed boys who are good readers) using a fast MR spectroscopic imaging technique called proton echo-planar spectroscopic imaging (1-cm(3) voxel resolution). The area under the N-acetylaspartate (NAA) and lactate peaks was measured to calculate the lactate/NAA ratio in each voxel. RESULTS: Dyslexic boys showed a greater area of brain lactate elevation (2.33 ± SE 0.843 voxels) as compared with the control group (0.57 ± SE 0.30 voxels) during a phonological task in the left anterior quadrant. No significant differences were observed in the nonlanguage tasks. CONCLUSION: Dyslexic and control children differ in brain lactate metabolism when performing language tasks, but do not differ in nonlanguage auditory tasks.